Terguride--a new dopamine agonist drug: a comparison of its neuroendocrine and side effect profile with bromocriptine. - Ciccarelli, E; Touzel, R; Besser, M; Grossman, A (1988)
Terguride, the C9-10 dihydrogenated derivative of lisuride, is a new drug which inhibits pituitary prolactin (PRL) secretion. It has mixed dopaminergic-antidopaminergic and alpha 2-antiadrenergic activity, and has proved useful in the clinical management of hyperprolactinemia. However, no trial comparing its use with the standard dopamine agonist bromocriptine has been reported. We have therefore compared three doses of terguride with bromocriptine 2.5 mg and placebo in a randomized double-blind crossover trial in eight normal volunteers. Terguride showed a potent dose-dependent PRL-inhibiting and growth hormone (GH)-releasing effect, while no significant changes were observed in thyroid-stimulating hormone (TSH), follicle-stimulating hormone (FSH), or luteinizing hormone (LH) in comparison to placebo. The neuroendocrine profile of terguride 1 mg was identical to that of bromocriptine, with a significant reduction in PRL still evident at 24 hours. However, in this small group of normal subjects, the side effects experienced at any dose of terguride were significantly less than with bromocriptine. Terguride 1 mg was always preferred to bromocriptine, while the lower doses were indistinguishable from placebo. Terguride is therefore likely to play an important role in the treatment of hyperprolactinemia.